Potential use of social networking tool to assist reading comprehension: implications for practice and future research - Yusop, F.D.; Chin, Y.L. (2011)
From a social constructivist viewpoint, reading is viewed as a social practice. The emergence of Web 2.0 tools such as blogs, wikis and social networking sites, provide wide opportunities to generate active interactions among learners in and out of the classroom. Unlike students in the past who were receptive learners of knowledge and in the reading context ‘mute outsiders’, students today are encouraged to be active constructors of their own learning environment. They are encouraged to learn not as isolated individuals, but as active members of society. This paper aims to examine the features of social networking sites with particular emphasis given to Edmodo, a secure social learning network for teachers and students, and the potential use of Edmodo in improving reading comprehension among young adult learners of English as a Foreign Language (EFL). The findings suggest that Edmodo can be potentially beneficial to the teaching and learning of reading due to several reasons: (1) positive learners’ perceptions and attitudes, (2) the likelihood of improved performance and (3) opportunities for engagement among the community of practice. Pedagogical implications for integration of social networking in teaching and learning are also discussed.